Penentuan Nilai Iodine Value, Cold Point, Melting Point dan Free Fatty Acid (FFA) pada Produk RBDPOL dan RBDPS di PT. Wilmar Nabati Padang - Arnum, Putri Pramana; Beri, Deski (TSAQOFAH, 2026)
Quality control of palm oil derivative products is an important aspect to ensure that the quality of RBDPOL and RBDPS complies with industry standards. This study aims to determine the Iodine Value, Cloud Point, Melting Point, and Free Fatty Acid (FFA) values of RBDPOL and RBDPS products at PT Wilmar Nabati Indonesia Teluk Bayur Padang Unit. This study used a quantitative descriptive approach with a laboratory practice method. The research samples consisted of RBDPOL IV-56, RBDPOL IV-58, and RBDPS taken directly from production points using jar bottles. Data were collected through laboratory testing, observation, and focused discussions with mentors and the Head of Quality Control. The results showed that RBDPOL IV-56 met PORAM standards for all parameters tested, with an Iodine Value of 56.25–56.91 I₂/100 g, a Cloud Point of 9.6–9.8°C, and a Melting Point of 21.2–21.8°C. RBDPOL IV-58 mostly met the standards, although some Iodine Value and Cloud Point values did not meet the standards at the initial stage of testing. Meanwhile, RBDPS showed Melting Point values that met the standards, whereas several Iodine Value values in the initial period were still below the standards. These findings confirm that laboratory analysis plays an important role in quality control of CPO processed products. The practical contribution of this study lies in strengthening applied understanding of the implementation of chemical analysis in quality control processes in the palm oil industry.